PENINGKATAN SELF CONFIDENCE DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN - Ardianti, Titin; Napfiah, Siti; Sunuyeko, Nurcholis; Rochsun (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This research was conducted because of the low self-confidence and mathematical communication skills of class VII students, especially in statistics. This is because Daarul Ukhuwwah Middle School has its own curriculum and there is no statistics material. Therefore, students do not have the courage to express their ideas or opinions. So, to increase self-confidence and mathematical communication skills of female students, researchers use cooperative learning with the time token method. The purpose of this study is to find out the description of the application of the time token type of cooperative learning to increase students' self-confidence and mathematical communication on set material in class VII SMP Daarul Ukhuwwah 2 Singosari Malang. The type of research used in this research is classroom action research (CAR). The subjects of this study were class VII-B students of SMP Daarul Ukhuwwah 2 Singosari for the 2022/2023 academic year consisting of 31 students. The data collection instruments used in this study were student observation sheets, questionnaires, and tests. This research was conducted in 1 cycle consisting of 2 meetings. The stages carried out in each cycle are planning, action, observation, and reflection. The results of this study indicate an increase in self-confidence and students' mathematical communication skills at each meeting. The average result of the questionnaire was 47.42% before the action became 69.50% in the first cycle of the 1st meeting to 83.23% in the 2nd meeting of the first cycle and from the average results of the test, namely 52.21% to 71, 60% in the first cycle of the 1st meeting to 86.45% in the 1st cycle of the 2nd meeting.